Application of eye-tracking in assessing the role of mediator variable (brand awareness) in the relation between packaging elements and customers' choice. (1st October 2021) - Salehi, Somayeh; Sanayei, Ali; Sammaknejad, Negar; Kazemi, Ali
The objective of this study is to assess the packaging elements that affect customers' choices through an indirect tool (SMI RED250). The focus here is to find which elements of the packaging affect consumers' choices in selecting the exposed product. Two tasks relating to a restaurant and health clinic were introduced and distributed to the participants in a random manner. In these two tasks, the participants were instructed to choose among five brands of Camel-Doogh for consumption in a restaurant or health clinic. The statistical sample consisted of 30 students and staff members from the University of Shahid Beheshti in Tehran, Iran, in running the experiment. The eye-tracker measured the participants' visual attention regarding these tasks. Measuring the level of attention and determining which packaging elements contribute to product selection can lead to more success in marketing a new product to the target market. The obtained results indicate that in the restaurant task, only the visual elements had a significant positive correlation with the individual's choice. In the health clinic task, the visual elements led directly to product selection, and verbal elements led indirectly to product selection through brand awareness.